(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
This article examines the interrelationship between gender equality and the concept of human dignity from a socio-philosophical perspective, focusing on the experience of Uzbekistan. The study analyzes gender equality not merely as a legal principle but as a value-based and human-centered phenomenon closely connected with dignity, justice, freedom, and social development. Employing ontological, axiological, and praxeological approaches, the research explores how gender equality contributes to the realization of human dignity in contemporary society. Particular attention is paid to the reforms implemented in New Uzbekistan, relevant national legislation, and the theoretical contributions of global scholars. The findings demonstrate that gender equality serves as a significant mechanism for strengthening human dignity, social cohesion, and sustainable development. The article proposes a conceptual model illustrating the dialectical relationship between gender equality and human dignity within the context of social modernization.